Pengaruh Pengembangan Media Ajar Visual Terhadap Siswa Sekolah Dasar dalam Memahami Konsep Matematika Secara Visual - Sabrina, Nasywa Assyifa; Maharaja, Loviana R; Naingglan, Monika More; Gaol, Marintan Lumban (Jurnal Pendidikan Matematika, 2023)
The aim of this research is to determine the effect of developing visual teaching media on elementary school students in understanding mathematical concepts. The method used in this research is a literature study method with a qualitative approach. Literature study is a research method carried out by collecting, studying and analyzing references or sources obtained in writing or in written form such as books, journals, articles, documents and other sources of information that are significant to the topic/title to be researched. The data analysis technique used in this research is by collecting data, analyzing the data and drawing conclusions. The data collection technique involves collecting several previous studies to answer how visual learning media influences students' understanding of mathematics.